Structural Investigation of Pyridinecarboxylato Titanium(IV) Complexes: An Uncommon Monomeric Octacoordinated Complex vs. a Hexaprismatic Architecture. Issue 2 (28th November 2013) - Fenton, Julie L.; Laaroussi, Anasse; Mobian, Pierre; Chaumont, Clément; Khalil, Georges; Huguenard, Clarisse; Henry, Marc
Abstract: We report the synthesis and structural characterisation of two titanium(IV) complexes. A new titanium(IV) complex bearing four picolinato ligands, denoted as Ti(pic)4, has been prepared under solvothermal conditions. This complex identified by single‐crystal diffraction is a new example of an octacoordinated environment for titanium(IV) and is close to an ideal triangular dodecahedron. A second synthesis of a hexaprismatric carboxylato titanium complex formulated as [Ti6 (μ3 ‐O)6 (O i Pr)6 (μ‐O2 CC5 H3 NCOO i Pr)6 ] starting from a dissymmetric anhydride pyridine carboxylic precursor is described. The solid‐state analysis shows the presence of a single compound among 13 possible species. Calculations gave evidence of a highly selective mechanism leading to the formation of the final product. Abstract : The structural characterisation of two titanium(IV) complexes bearing pyridinecarboxylato ligands is reported. An uncommon octacoordinated complex was obtained by treating picolinic acid with titanium isopropoxide. A second complex formulated as [Ti6 (μ3 ‐O)6 (O i Pr)6 (μ‐O2 CC5 H3 NCOO i Pr)6 ] was prepared from titanium isopropoxide and a dissymmetric anhydride pyridine carboxylic precursor.